Documenting trumpet leaf-miner moths (Tischeriidae): new Neotropical Coptotriche and Astrotischeria species, with notes on Sapindaceae as a host-plant family - Stonis, Jonas R.; Diškus, Arūnas; Remeikis, Andrius; Fernández-Alonso, José L.; Baryshnikova, Svetlana V.; Solis, M. Alma (Zootaxa, 2021)
Four new species of trumpet leaf-miner moths (Tischeriidae) are described from the Neotropics: Coptotriche serjaniphaga Remeikis & Stonis, sp. nov., feeding on Serjania Mill. (Sapindaceae), Astrotischeria mystica Diškus & Stonis, sp. nov., feeding on Verbesina L. (Asteraceae), A. yungasi Diškus & Stonis, sp. nov., feeding on Oyedaea DC. (Asteraceae), and A. parapallens Diškus & Stonis, sp. nov., feeding on Baccharis L. (Asteraceae). Records on Sapindaceae-feeding Tischeriidae are very rare and Serjania is a novel host-plant genus for Tischeriidae. It is hypothesized that Serjania, a diverse genus in the tropical and subtropical Americas, may be a host for many undiscovered species of specialized stenophagous Tischeriidae. The new species are illustrated with photographs of the adults, male and, if available, female genitalia, and the leaf mines. We briefly discuss the importance of new species descriptions as a part of biodiversity assessment.